Implementation of Police Regulation Number 7 of 2022 concerning the Professional Code of Ethics for the National Police of the Republic of Indonesia - Indriana, Era; Muhibbin , Moh; Suratman, Suratman (Universitas Medan Area, 2024)
This examination is experimental juridical exploration, and that implies lawful examination in regards to the application or execution of regularizing legitimate arrangements in real life at every particular legitimate occasion that happens in the public arena. The justification for utilizing experimental juridical exploration is to give an outline of all that is genuinely connected with the execution of Perpol No. 7 of 2022 concerning the Police Proficient Set of rules. The exploration approach utilized in this examination is a humanistic juridical methodology. The exploration approach was done in view of a lawful issue. The implementation of Regulation No. Training for police officers on information dissemination, internal supervision, investigation of violations, imposition of sanctions, public accountability, reporting violations, and prevention of violations has been implemented under Law No. 7 of 2022. Aside from that, in carrying out Perpol no. 7 of 2022, has given understanding to cops to focus on state morals, institutional morals, local area morals and character morals.